2018
DOI: 10.1186/s12915-018-0576-6
|View full text |Cite
|
Sign up to set email alerts
|

VOPP1 promotes breast tumorigenesis by interacting with the tumor suppressor WWOX

Abstract: BackgroundThe WW domain-containing oxidoreductase (WWOX) gene, frequently altered in breast cancer, encodes a tumor suppressor whose function is mediated through its interactions with cancer-related proteins, such as the pro-apoptotic protein p73α.ResultsTo better understand the involvement of WWOX in breast tumorigenesis, we performed a yeast two-hybrid screen and co-immunoprecipitation assays to identify novel partners of this protein. We characterized the vesicular overexpressed in cancer pro-survival prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…VOPP1 overexpression has been observed in several tumor types, such as gastric cancer, head and neck squamous carcinoma and glioma (51)(52)(53). A recent study reported that VOPP1 can promote breast cancer development by interacting with the tumor suppressor WW domain containing oxidoreductase (54). These results suggest that VOPP1 may serve an important role in TNBC carcinogenesis and could be exploited to develop therapies for patients with TNBC.…”
Section: Discussionmentioning
confidence: 92%
“…VOPP1 overexpression has been observed in several tumor types, such as gastric cancer, head and neck squamous carcinoma and glioma (51)(52)(53). A recent study reported that VOPP1 can promote breast cancer development by interacting with the tumor suppressor WW domain containing oxidoreductase (54). These results suggest that VOPP1 may serve an important role in TNBC carcinogenesis and could be exploited to develop therapies for patients with TNBC.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, reciprocal co-IP with all of the partners for each interaction was observed (Figure 3A). Very recently, Bonin et al (46) have also identified VOPP1 as a WWOX interactor in human cells by means of yeast-two hybrids and demonstrated that the WW1 region is the interacting domain mostly with the 162 PPPY 165 motif of VOPP1.…”
Section: Resultsmentioning
confidence: 99%
“…VOPP1 protein structure includes a transmembrane domain and it was reported to partially co-localize with perinuclear lysosomes, suggesting that VOPP1 containing vesicles enter and participate in final lysosomal pathways (54). Very recently, Bonin et al (46). using a yeast-two-hybrid system and co-IP reported that VOPP1 physically interacts with WWOX.…”
Section: Discussionmentioning
confidence: 99%
“…36 Recently, Bonin et al indicated that VOPP1 contributes to breast cancer progression. 37 Its role in CC is largely unknown. In our study, we found that VOPP1 was upregulated in CC tissues.…”
Section: Dovepressmentioning
confidence: 99%